A survey assessing sleep efficiency among Saudis during COVID-19 home confinement using the Pittsburgh sleep quality index: A call for health education - Saad S. Alqahtani; David Banji; Otilia J.F. Banji (Elsevier, 2021)
The COVID-19 pandemic has introduced uncertainties that have disrupted regular routines. Sleep may be adversely affected by stressful circumstances that jeopardize general health. Hence, the impact of home confinement on the sleep efficiency of the general population was assessed.An online survey was conducted by using the Pittsburgh sleep quality index (PSQI) to assess sleep duration, sleep efficiency, latency to fall asleep, and global PSQI score. Questions pertaining to demography, home confinement, and anxiety were included. Data was collected from the residents of the Southwestern region from April 15, 2020 to May 15, 2020. Data were analyzed through bivariate, multivariate logistic regression, and independent t tests.A total of 593 subjects responded to the survey. Males (OR 1.92 [1.3-2.7], p < 0.001), and subjects aged ≥51 years (OR 2.49 [1.3-4.4], p = 0.002) were more likely to be poor sleepers (<6 h). In hypertensive subjects, inadequate sleep was twice as high (OR 2.2 [1.1-4.4], p < 0.05) than other comorbidities. Males were less likely to have sleep latency (OR 0.58 [0.40-0.86], p = 0.005) but smoking increased the latency of falling asleep (OR 2.41 [1.47-4.0], p < 0.001). Sleep duration was significantly influenced by home confinement (p = 0.002), whereas sleep duration (p = 0.001), latency (p = 0.018), sleep efficiency (p = 0.005), and global PSQI scores (p = 0.005) were significantly affected by anxiety.In the southwestern region, we found sleep influenced by anxiety about COVID-19. Community pharmacists are the most accessible health care professionals and could play a pivotal role in educating the lay public on the importance of sleep hygiene through posters displayed in pharmacies and with the help of public education material.